1995
DOI: 10.1037/0021-843x.104.2.346
|View full text |Cite
|
Sign up to set email alerts
|

Onset and staging of DSM-IV alcohol dependence using mean age and survival-hazard methods.

Abstract: Orderly onset of psychiatric symptoms has implications for both case detection and the construct validity of the underlying illness. Mean age and survival-hazard techniques were used to study the onset of alcohol abuse and dependence (as defined in the 4th edition of the Diagnostic and Statistical Manual of Mental Disorders; American Psychiatric Association, 1994) in 369 clinical cases drawn from a heterogeneous regional sample. The methods provided a similar general pattern of symptom sequencing, though only … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

10
86
2
1

Year Published

2002
2002
2016
2016

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 109 publications
(99 citation statements)
references
References 20 publications
10
86
2
1
Order By: Relevance
“…Specifically, results of the present study, establishing that the ICS predicts problem drinking cross-sectionally in young adults with relatively brief drinking histories, further support the position that impairment of control is one of the earliest stages of addiction (Chick and Duffy, 1979;Langenbucher et al, 1995;Martin et al, 1996;Winters et al, 1999). By the time later stages are reached (e.g., withdrawal and alcohol-induced psychological or physical problems), risk of relapse increases (Witkiewicz and Marlatt, 2004), making treatment more difficult.…”
Section: Discussionsupporting
confidence: 57%
See 1 more Smart Citation
“…Specifically, results of the present study, establishing that the ICS predicts problem drinking cross-sectionally in young adults with relatively brief drinking histories, further support the position that impairment of control is one of the earliest stages of addiction (Chick and Duffy, 1979;Langenbucher et al, 1995;Martin et al, 1996;Winters et al, 1999). By the time later stages are reached (e.g., withdrawal and alcohol-induced psychological or physical problems), risk of relapse increases (Witkiewicz and Marlatt, 2004), making treatment more difficult.…”
Section: Discussionsupporting
confidence: 57%
“…Impaired control is not only an important element of addiction in general, it is of particular relevance to young adults and others with relatively brief drinking histories given its early emergence. Heavy drinking adolescents often report impaired control, as have adults with problem drinking histories who were asked to recount which of their dependence symptoms developed the earliest (Chick and Duffy, 1979;Langenbucher and Chung, 1995). This is in contrast with DSM-IV dependence criteria like withdrawal and alcohol-induced physical or psychological problems (APA, 1994), which typically require lengthy drinking histories and are rarely reported by adolescents (Martin et al, 1996;Winters et al, 1999).…”
Section: Introductionmentioning
confidence: 87%
“…These aims were addressed with data from a community-recruited longitudinal study of adolescent girls because this developmental period is a high-risk time for onset of substance abuse (Langerbucher & Chung, 1995), depression (Hankin et al, 1998), and eating pathology (Stice, Killen et al, 1998), and because bulimic pathology is rare among males.…”
Section: Overview Of Studymentioning
confidence: 99%
“…Regardless of whether DSM-III-R (American Psychiatric SAHA ET AL. 369 Association, 1987) or DSM-IV criteria were used, those studies consistently indicated the presence of two correlated but distinct factors.Previous studies have identifi ed considerable overlap between DSM-IV criteria for abuse and dependence (Langenbucher and Chung, 1995;. Even factor analytic studies that report two-factor models do not yield complete differentiation between abuse and dependence criteria Harford and Muthén, 2001;Muthén, 1995).…”
mentioning
confidence: 99%